2011
DOI: 10.1111/j.1472-4642.2011.00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Spread of common species results in local-scale floristic homogenization in grassland of Switzerland

Abstract: Aim We assess changes in plant species richness and changes in species dissimilarity at local scale in Swiss grassland between the time periods 2001-2004 and 2006-2009. Further, we provide an ecological interpretation of the observed taxonomic homogenization of vascular plants. Location Switzerland. Methods Changes in species richness and changes in Simpson dissimilarity index of vascular plants in grassland (meadows and pastures) were examined. The analyses were based on species lists recorded on 339 10-m 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 35 publications
3
46
1
Order By: Relevance
“…Furthermore, across a range of terrestrial and aquatic organisms, Baiser et al (2012) found that the biotic homogenization at a broad scale (regional to continental) was more attributable to the changes in species richness than the reductions in spatial turnover. Our result based on the local scale contrasts with this broad-scale finding, likely resulting from differences in the factors reshuffling communities at different spatial scales (Bühler and Roth 2011;Karp et al 2012;Trentanovi et al 2013). At larger scales, the processes behind the observed changes in species richness may be explained by biogeographical theories such as the interplay between immigration and extinction (Baiser et al 2012).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Furthermore, across a range of terrestrial and aquatic organisms, Baiser et al (2012) found that the biotic homogenization at a broad scale (regional to continental) was more attributable to the changes in species richness than the reductions in spatial turnover. Our result based on the local scale contrasts with this broad-scale finding, likely resulting from differences in the factors reshuffling communities at different spatial scales (Bühler and Roth 2011;Karp et al 2012;Trentanovi et al 2013). At larger scales, the processes behind the observed changes in species richness may be explained by biogeographical theories such as the interplay between immigration and extinction (Baiser et al 2012).…”
Section: Discussionmentioning
confidence: 48%
“…The resultant nestedness component is also referred to as "richness difference," which represents how differences in species richness that are not due to species turnover contribute to patterns of the overall β-diversity (Legendre 2014). Notably, several recent studies have shown that biotic homogenization sometimes occurs despite no net change in local species richness (α-diversity) (Bühler and Roth 2011;McCune and Vellend 2013;Rodrigues et al 2013), which is in contrast to the well-documented patterns of biotic homogenization associated with a net loss of biodiversity resulting from the response of sensitive specialist species to habitat modifications (Clavel et al 2011). Considering such variable effects of local species richness on the spatial variations of communities among localities, separating the effects of α-diversity from the overall β-diversity will be an important step to further help understand the causes and consequences of biotic homogenization.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 98%
“…Examples in this study could be Scorzoneroides autumnalis, Trifolium pratense and Prunella vulgaris, which are common grassland 'generalists'. It is likely that a longer time period is needed to assess such changes particularly in grasslands where most of the species are perennials (Bühler and Roth 2011). In addition to the indication of greater homogenization at the regional level, the significant decrease in site species richness suggests that within-site diversity has also declined.…”
Section: Turnover In Target Meadow Speciesmentioning
confidence: 99%
“…Bühler and Roth (2011) found that taxonomic homogenization was a result of an increase in more common species. Examples in this study could be Scorzoneroides autumnalis, Trifolium pratense and Prunella vulgaris, which are common grassland 'generalists'.…”
Section: Turnover In Target Meadow Speciesmentioning
confidence: 99%
See 1 more Smart Citation